Kinetics of cone specific G-protein signaling in avian photoreceptor cells - Yee, Chad; Görtemaker, Katharina; Wellpott, Rieke; Koch, Karl-Wilhelm (Frontiers in Molecular Neuroscience, 2023)
Cone photoreceptor cells of night-migratory songbirds seem to process the primary steps of two different senses, vision and magnetoreception. The molecular basis of phototransduction is a prototypical G protein-coupled receptor pathway starting with the photoexcitation of rhodopsin or cone opsin thereby activating a heterotrimeric G protein named transducin. This interaction is well understood in vertebrate rod cells, but parameter describing protein–protein interactions of cone specific proteins are rare and not available for migratory birds. European robin is a model organism for studying the orientation of birds in the earth magnetic field. Recent findings showed a link between the putative magnetoreceptor cryptochrome 4a and the cone specific G-protein of European robin. In the present work, we investigated the interaction of European robin cone specific G protein and cytoplasmic regions of long wavelength opsin. We identified the second loop in opsin connecting transmembrane regions three and four as a critical binding interface. Surface plasmon resonance studies using a synthetic peptide representing the second cytoplasmic loop and purified G protein α-subunit showed a high affinity interaction with a KD value of 21 nM. Truncation of the G protein α-subunit at the C-terminus by six amino acids slightly decreased the affinity. Our results suggest that binding of the G protein to cryptochrome can compete with the interaction of G protein and non-photoexcited long wavelength opsin. Thus, the parallel presence of two different sensory pathways in bird cone photoreceptors is reasonable under dark-adapted conditions or during illumination with short wavelengths.